Asia 2050: Realizing the Asian Century - Edited by Kohli, Harinder S.; Sharma, Ashok and Sood, Anil (Los Angeles SAGE, 2011)
This study, Asia 2050: Realizing the Asian Century, is aimed at key opinion makers to foster debate on a vision of and strategy for Asia's potentially historic rise among the global community of nations between now and 2050. It offers a long-term perspective of the Asia region as a whole as opposed to the more common approach that delivers a short- to medium-term perspective of selected countries, subregions or issues.
Includes Colored Illustrations, Index, and References.
Keywords: Asia -- Economic conditions -- 21st Century